2015
DOI: 10.1016/j.trb.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Compound Gamma representation for modeling travel time variability in a traffic network

Abstract: a b s t r a c tThis paper proposes a compound probability distribution approach for capturing both vehicle-to-vehicle and day-to-day variability in modeling travel time reliability in a network. Starting from the observation that standard deviation and mean of distance-normalized travel time in a network are highly positively correlated and their relationship is well characterized by a linear function, this study assumes multiplicative error structures to describe data with such characteristics and derives a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The values of these four measures were then fitted to a family of probability densities called "Johnson" curves. In order to capture both the vehicleto-vehicle and day-to-day variability in travel time data, Kim and Mahmassani [9] proposed a Gamma-Gamma mixture distribution model. Based on their proposed model, the heterogeneity within these two variability types under different weather conditions can be described as well.…”
Section: Introductionmentioning
confidence: 99%
“…The values of these four measures were then fitted to a family of probability densities called "Johnson" curves. In order to capture both the vehicleto-vehicle and day-to-day variability in travel time data, Kim and Mahmassani [9] proposed a Gamma-Gamma mixture distribution model. Based on their proposed model, the heterogeneity within these two variability types under different weather conditions can be described as well.…”
Section: Introductionmentioning
confidence: 99%
“…In both figures, a linear trend can also be seen between the spatial mean density k and the spatial heterogeneity σ k . This trend was noticed by Knoop, Hoogendoorn, and Van Lint (2012), and by Mahmassani, Hou, and Saberi (2013); Kim and Mahmassani (2015) about the variability in travel times.…”
Section: Single Reservoir Implementation Of the Mfd-based Modelmentioning
confidence: 54%
“…Other researchers studied the relationship between average travel time per unit distance and standard deviation of travel time (see for example [30,[33][34][35]), and also optimal routes across a potential network (see for example [2,36]). Kim et al [37] proposed a mixed gamma distribution for modeling the variations of travel time across a road network. They found that the mixed gamma distribution is the best distribution for travel time estimation, with different dimensions of changes in relation to daily variations and vehicle type.…”
Section: Literature Reviewmentioning
confidence: 99%